PLEASE HELP IT’S TIMED
![PLEASE HELP ITS TIMED class=](https://us-static.z-dn.net/files/de4/665e17342853d4c50b2027686cb6b47f.png)
Answer:
a = -
b = -
c = 9
d = 3
e = 3
f = 2
Step-by-step explanation:
First we will solve the expression:
[tex]\frac{3x}{2x-6}+\frac{9}{6-2x}[/tex]
Solving:
First we will take negative sign common, then take LCM of denominator and simplify the expression.
[tex]=\frac{3x}{2x-6}+\frac{9}{\textbf{-}(2x-6)}\\=\frac{3x}{2x-6}+\frac{\textbf{-}9}{(2x-6)}\\Taking\:LCM\\=\frac{3x-\mathbf{9}}{2x-6}\\=\frac{\mathbf{3}(x-\mathbf{3})}{\mathbf{2}(x-3)}\\=\mathbf{\frac{3}{2}}[/tex]
So, After solving we get:
a = -
b = -
c = 9
d = 3
e = 3
f = 2